Assessment of hypoglycemic activity of the aqueous extract of Abuta grandifolia (Mart.) in diabetic rats induced by alloxan - Justil, Carlos (2015)
Abuta grandifolia is a native plant from the Amazon region, traditionally used in the control of diabetes mellitus. The aim of the present study was to evaluate the effectiveness of reducing the glucose level when the aqueous extract (AE) ofA. grandifolia (Mart.) is orally administered in diabetic rats induced by alloxan. Thirty Sprague Dawley male rats, 3-month-old, body weight of 240 ± 10 g were used. The animals were distributed in six groups (negative control, positive control, treated with three doses of the AE [100, 250 and 500 mg/kg] and treated with glibenclamide [10 mg/kg]). Diabetes was induced by intraperitoneal injection of alloxan (100 mg/kg). Blood glucose levels were measured by an electronic glucometer (Accu-ChekActive). The glibenclamide and the AE ofA. grandifolia in doses of 100 and 250 mg/kg showed a hypoglycemic effect; however, the 250 mg/kg dose had the best effect between 6 and 72 hour post administration. It is concluded that AE of A. grandifolia (Mart.) (oral dose of 250 mg/kg) decreased blood glucose (p<0.05) in diabetic rats induced by alloxan.